PENGARUH RETURN ON ASSET DAN CURRENT RATIO TERHADAP HARGA SAHAM PADA PT. ULTRAJAYA MILK INDUSTRY & TRADING COMPANY TBK PERIODE 2014-20203 - Amanda, Shella; Kamal, Fahmi; Koto3, Deni I Indra Purnama (Journal MISSY (Management and Business Strategy), 2025)
This study analyzes the effect of Return On Asset (ROA) and Current Ratio (CR) on the stock price of PT Ultrajaya Milk Industry & Trading Company Tbk for the period 2014–2023. The focus is on the extent to which ROA and CR influence stock price fluctuations. The method employed is quantitative, utilizing financial statement data and stock data. Analysis is conducted through descriptive and statistical approaches, including classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). Results show that ROA and CR significantly affect stock prices, with t-values of 33.557 and 11.603, respectively, and an F-value of 569.729. The regression equation Y = 34.40 - 84.28(X1) + 81(X2) indicates ROA has a negative effect while CR has a positive effect. The adjusted R² value of 0.992 explains 99.2% of the stock price variation.